Correction: The deeper, the more distinct: dissolved organic matter composition differs between soil types and diverges with depths - Charamba, Livia V. C.; Houska, Tobias; Kaiser, Klaus; Knorr, Klaus-Holger; Krause, Tobias; Chen, Huan; Krám, Pavel; Hruška, Jakub; Müller, Ingo; Kalbitz, Karsten (Frontiers in Environmental Science, 2026)
Graphical AbstractDiagram illustrating site-specific and depth-specific dissolved organic matter (DOM) composition changes. It features four soil types: Peat, Peaty Gleysol, Podzol, and Cambisol, each with processes like anaerobic preservation and microbial processing. Depth-specific changes are shown with arrows, indicating how shared compounds' abundance alters with depth. The right side shows surface water flow.